Total synthesis of each enantiomer of falcarinol and panaxjapyne A via asymmetric catalytic alkynylation of an aldehyde. Issue 7 (15th April 2015) - Yang, Yan-Qing; Li, Shuo-Ning; Zhong, Jiang-Chun; Zhou, Yun; Zeng, Hao-Zhe; Duan, Hong-Jie; Bian, Qing-Hua; Wang, Min
Graphical abstract